ADVANCEMENTS IN UNDERSTANDING AND MANAGING ALCOHOL WITHDRAWAL SYNDROME: A COMPREHENSIVE REVIEW - SINGH, AJEET PAL; SHARMA, ASHISH KUMAR; SINGH, THAKUR GURJEET (International Journal of Current Pharmaceutical Research, 2024)
Alcohol withdrawal syndrome (AWS) is a clinically significant condition that can arise upon abrupt cessation or reduction of alcohol consumption in individuals with alcohol dependence. This review article provides a comprehensive overview of AWS, encompassing its epidemiology, pathophysiology, clinical manifestations, assessment tools, and management strategies. We discuss the neurobiological mechanisms underlying AWS, including the role of neurotransmitter systems such as gamma-aminobutyric acid (GABA) and glutamate, as well as neuroadaptive changes that occur with chronic alcohol use. Furthermore, we explore the spectrum of clinical manifestations associated with AWS, ranging from mild withdrawal symptoms to severe complications such as delirium tremens and seizures. Diagnostic tools and scoring systems commonly used for assessing AWS severity are examined, along with evidence-based approaches for pharmacological and non-pharmacological management of AWS. Additionally, we highlight emerging research areas and future directions in the field of AWS, including novel treatment modalities and potential biomarkers for predicting withdrawal severity and treatment response. This comprehensive review aims to provide clinicians, researchers, and healthcare professionals with a thorough understanding of AWS to facilitate early recognition, appropriate management, and improved outcomes for individuals affected by this condition.